The formation environment of potassic‐chloro‐hastingsite in the nakhlites MIL 03346 and pairs and NWA 5790: Insights from terrestrial chloro‐amphibole. (25th July 2016) - Giesting, Paul A.; Filiberto, Justin
Abstract: Potassic‐chloro‐hastingsite has been found in melt inclusions in MIL 03346, its paired stones, and NWA 5790. It is some of the most chlorine‐rich amphibole ever analyzed. In this article, we evaluate what crystal chemistry, terrestrial analogs, and experiments have shown about how chlorine‐dominant amphibole (chloro‐amphibole) forms and apply these insights to the nakhlites. Chloro‐amphibole is rare, with about a dozen identified localities on Earth. It is always rich in potassium and iron and poor in titanium. In terrestrial settings, its presence has been interpreted to result from medium to high‐grade alteration (>400 °C) of a protolith by an alkali and/or iron chloride‐rich aqueous fluid. Ferrous chloride fluids exsolved from mafic magmas can cause such alteration, as can crustal fluids that have reacted with rock and lost H2 O in preference to chloride, resulting in concentrated alkali chloride fluids. In the case of the nakhlites, an aqueous alkali‐ferrous chloride fluid was exsolved from the parental melt as it crystallized. This aqueous chloride fluid itself likely unmixed into chloride‐dominant and water‐dominant fluids. Chloride‐dominant fluid was trapped in some melt inclusions and reacted with the silicate contents of the inclusion to form potassic‐chloro‐hastingsite.